2011
DOI: 10.1016/j.socscimed.2011.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Hispanic immigrant women’s perspective on healthy foods and the New York City retail food environment: A mixed-method study

Abstract: Much has been written about the role of dietary acculturation in the epidemic of obesity among Hispanic immigrants in the United States. Yet little is known about the role of beliefs and preferences in immigrants’ dietary practices and their relationship to the retail food environment in which the practices occur. We conducted a mixed-methods convergence study of these issues. Twenty eight foreign-born Hispanic adult women, recruited from families enrolled in a childhood asthma study and mainly living in New Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 47 publications
(75 reference statements)
2
57
0
Order By: Relevance
“…Furthermore, this study showed that the geographic access or physical factors related to the food environment directly influence the kind of food that immigrants can access, which echoes past research. 19,23 Such findings align with previous studies suggesting that areas in the Region of Waterloo are indeed food swamps on the basis of the high access to poor-quality food in RFOs.…”
Section: Experiences Of the Food Environmentsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, this study showed that the geographic access or physical factors related to the food environment directly influence the kind of food that immigrants can access, which echoes past research. 19,23 Such findings align with previous studies suggesting that areas in the Region of Waterloo are indeed food swamps on the basis of the high access to poor-quality food in RFOs.…”
Section: Experiences Of the Food Environmentsupporting
confidence: 89%
“…18 Recent work in Canada and elsewhere attempts to understand how individuals navigate their food environment. 17,[19][20][21][22][23] Beyond examining environmental factors related to geographic and economic access, there is an absence of research investigating additional factors, such as those within the socio-cultural and political realm, which are also related to diet and obesity.…”
mentioning
confidence: 99%
“…Farmers' market use is found to be higher among foreign-as compared to US-born Hispanic mothers [37]. In research with foreign-born Hispanic women, cultural preferences for fresh FV have been identified [38][39][40]. In one study, participants reported using FMNP vouchers, local produce from friends and neighbors, and produce grown by families themselves to acquire fresh FV they desired [38].…”
Section: Discussionmentioning
confidence: 99%
“…Farmers' markets are also associated with more healthful food consumption. For example, neighborhoods with farmers' markets had higher fruit and vegetable consumption rates among people of color 49 .…”
Section: Health Impactsmentioning
confidence: 99%